High sensitivity sapphire FBG temperature sensors for the signal processing of data communications technology - Mahmoud M. A. Eid; Ashraf S. Seliem; Ahmed Nabih Zaki Rashed; Abd El-Naser A. Mohammed; Mohamed Yassin Ali; Shaimaa S. Abaza (Institute of Advanced Engineering and Science, 2021)
This study has outlined the fiber bragg grating (FBG) temperature sensors signal processing for data communications by using OptiGrating simulation software. The reflectivity of the silica and sapphire fiber grating spectrum is reported against the grating wavelength for internal and external temperature variations. As well as apodized Gaussian reflectivity of the silica and sapphire fiber grating spectrum is simulated and clarified against the grating wavelength for high temperature variations. The temperature sensitivity of sapphire FBG nearly 0.11 pm/0C, where its value is three times higher than silica FBG. It is observed that silica and Sapphire FBG sensors were tested up to 1000 0C by using Gaussian apodization type, side lobes in reflectivity spectrum are totally suppressed.